In-Vitro Evaluation of Some Traditional Medicinal Plants on Calcium Oxalate Urolithiasis - . Abdel Bar, Fatma; Foudah, Ahmed; Majrashi, Amjad; Dossery, F. Al-; Galala, Amal (Emirates Journal of Food and Agriculture, 2022)
The prevalence of urolithiasis in Middle East countries is predominantly high. Traditional medicinal plants play a role in the prevention and management of urolithiasis. The effect of Petroselinum crispum, rind of Citrus sinensis L., rind of Citrus limon L., Ammi visnaga (L.) LAM., Tamarindus indica L., Nigella sativa L., Cymbopogon proximus Hochst. ex A. Rich., Hibiscus sabdariffa L., Hordeum vulgare L., and Cymbopogon schoenanthus (L.) Spreng. on calcium oxalate crystallization was investigated in-vitro. The antispasmodic activity on acetylcholine-induced contraction in rat ileum was also screened ex-vivo. A significant reduction in the mean diagonal of calcium oxalate crystals was observed for P. crispum, C. proximus, N. sativa, and C. limon (4.41 mm, 4.71, 5.44, and 5.67 mm, respectively) compared to the negative control (12.19 mm). H. sabdariffa exhibited antinucleation effect however, P. crispum showed a marked inhibition of calcium oxalate aggregation at 10 mg/mL after 60 min compared to the negative control. A remarkable ex-vivo antispasmodic activity was observed for C. proximus, C. schoenanthus, and A. visnaga extracts. Our results provide scientific evidence for the traditional use of the studied plant-derived products as potential therapies for calcium oxalate urolithiasis.